Intracameral recombinant tissue plasminogen activator (r-tPA) for refractory toxic anterior segment syndrome. Issue 2 (25th November 2013) - Dotan, Assaf; Kaiserman, Igor; Kremer, Israel; Ehrlich, Rita; Bahar, Irit
Abstract : Aims: To investigate the therapeutic effect of recombinant tissue plasminogen activator (r-tPA) in patients with refractory toxic anterior chamber segment syndrome after cataract surgery with posterior chamber intraocular lens implantation. Methods: This prospective cohort study was performed from May 2010 to November 2011 at a tertiary university-based medical centre. Forty patients (40 eyes) with an anterior chamber fibrin reaction after cataract surgery were treated with intracameral injection of r-tPA (25 µg/0.1 mL) following failure to respond to conventional treatment with intensive topical and subconjunctival steroids. Outcome measures were best-corrected visual acuity, clearance/recurrence of the fibrin reaction and complications. Corneal endothelial cell counts were evaluated before and after r-tPA injection (n=6). Results: Intracameral r-tPA injection was administered 10–49 days after cataract surgery; mean was 20.3±9.6 days after surgery. At 1 day after treatment, complete clearance of the fibrin reaction was observed in 32 patients (80%) and partial clearance in 8 (20%). At the 1-month evaluation, the reaction had completely resolved in 95% of patients. Mean visual acuity improved from 0.61±0.38 logMAR before treatment to 0.45±0.37 logMAR 1 month later (p=0.06). There were no statistically significant differences in improvement in visual acuity and fibrinolysis rate by time of r-tPA injection after surgery (10–15 days, n=16 vs 16–49 days, n=24). There were no cases of increased intraocular pressure or endophthalmitis following the procedure. Conclusions: Intracameral injection of 25 µg r-tPA is safe and effective for the treatment of refractory fibrin reaction after cataract surgery.